2020
DOI: 10.1155/2020/6630906
|View full text |Cite
|
Sign up to set email alerts
|

User Acceptance of Internet of Vehicles Services: Empirical Findings of Partial Least Square Structural Equation Modeling (PLS-SEM) and Fuzzy Sets Qualitative Comparative Analysis (fsQCA)

Abstract: Recently, IoV-based services and vehicles have come to the forefront as part of the growing market for the automobile industry. Since IoV-based services and vehicles were introduced, they have been expected to grow rapidly. However, contrary to optimistic expectations for future market growth, the IoV-based services and vehicles market has appeared to hit a roadblock and remains at an early market stage. Therefore, research of the determinants leading to consumers’ intention to accept and purchase IoV-based se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 115 publications
(348 reference statements)
1
14
1
Order By: Relevance
“…The configurations identify four of the seven possible variables as sufficient: high Technology Readiness, Effort Expectancy, Social Influence and Facilitating Conditions lead to the outcome of interest. This is in high contrast with existing studies on investigating user behavior through the lens of UTAUT2 model or Technology Readiness [5,9], in which identified configurations typically take a more complex form. In this study, the collected data shows a more straightforward, but not trivial, picture of why young elderly continue to use digital wellness services: if they perceive at least one of the four identified, core antecedents positively enough, this is sufficient to drive further use of the service.…”
Section: Configurations For High Level Of Intention To Continue Using Digital Wellness Servicescontrasting
confidence: 65%
See 1 more Smart Citation
“…The configurations identify four of the seven possible variables as sufficient: high Technology Readiness, Effort Expectancy, Social Influence and Facilitating Conditions lead to the outcome of interest. This is in high contrast with existing studies on investigating user behavior through the lens of UTAUT2 model or Technology Readiness [5,9], in which identified configurations typically take a more complex form. In this study, the collected data shows a more straightforward, but not trivial, picture of why young elderly continue to use digital wellness services: if they perceive at least one of the four identified, core antecedents positively enough, this is sufficient to drive further use of the service.…”
Section: Configurations For High Level Of Intention To Continue Using Digital Wellness Servicescontrasting
confidence: 65%
“…In a similar approach, Liang et al [5] investigate the impact of the UTAUT2 dimensions on technology adoption in an autonomous vehicle context. In assessing their structural model, they find only PE, price value (PV) and habit to be significant predictors of behavioral intention.…”
Section: Literature Review and Propositionsmentioning
confidence: 99%
“…Perceived risk means the potential problems and risks brought from the introduction of innovation [7], and it is the inhibitor for technology adoption [38,44,71]. Dialectically, everything has two sides.…”
Section: Technology Characteristics Of M-gov Cloudmentioning
confidence: 99%
“…In the same direction, recent 134 surveys in related contexts have shown that the consumers' intention to accept or purchase Internet-of-Vehicle (IoV) based services is generally low. Therefore, it is significant to explore the determinants of consumers' intention to accept and purchase IoV-based services (Liang et al, 2020). "A successful real-world deployment of innovative CV applications not only depends on their maturity and usability, but also hinges upon user acceptance" (Li et al, 2021, p. 1).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…For example the Theory of Reasoned Action (TRA) (Fishbein & Ajzen, 1975), technology acceptance model (TAM) (Davis, 1989), theory of planned behavior (TPB) (Ajzen, 1991), task-technology fit (TTF) (Goodhue & Thompson, 1995), motivational model (MM) (Davis et al, 1992), unified theory of acceptance and use of technology (UTAUT) (Venkatesh et al, 2003(Venkatesh et al, , 2012, initial trust model (ITM) (McKnight et al, 2002), diffusion of innovation theory (IDT) (Rogers, 2010), and social cognitive theory (SCT) (Compeau et al, 1999). Numerous investigations have employed these frameworks in their original form or augmented them with novel constructs, resulting in the formulation of models that serve as conduits for their research endeavors across diverse technological contexts (Liang et al, 2020). Nonetheless, within context-specific investigations concerning acceptance, two models frequently assume foundational roles (Lee et al, 2003) and are concisely elucidated in the ensuing discussion.…”
Section: Models Of Technology Acceptancementioning
confidence: 99%